RESPON ORANG TUA SISWA SUKU SAKAI TERHADAP INFRASTRUKTUR SEKOLAH DI SDN 26 MANDAU KOTA DURI KABUPATEN BENGKALIS - Wulandari, Nila Sarifah; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The tribal circles of Sakai at Pematang Pudu Urban Village now already growing their wish in education sector. Hovewer which is a pity, government still careless about progress for their. That matter aimed at only one public school at there and still a elementary school (SD), that is SDN 26 Mandau. Now still much happens deficienies in the school infrastructure at that school than oher elementary school at Duri City. When it should be the school at settlements that just developing in education sector must be pay attention to its condition so that they more be spirit to studying. Now still visible happen a marginalization to the tribal circles of Sakai at Pematang Pudu Urban Village, Duri City, Bengkalis District. The purpose of this research are for knowing about the parent’s reactions of Sakai students, the parent’s responses of Sakai students, and the parent’s reasons of Sakai students for choosing send to school their childs at SDN 26 Mandau. Main theory of this research is Social Response Theory, support theory other is Marginal Theory. This research using quantitative descriptive to analysis  method with kind of this research is survey based on that location and object situation. Research result concluded that the parents’s responses of Sakai students more dominant be positive to school infrastructure at SDN 26 Mandau, because of the research results show 86% positive responses and 14% negative responses. Extrinsic reasons of respondents send to school their childs at SDN 26 Mandau are because a short distance, not paying SPP, the majority of residents send to school their childs at there, and attractive enviromental conditions. Intrinsic reasons of respondents are because they feel public school is government responsibility and they feel their childs can better protected if studying at elementary school that have a short distance of home.Keywords : Response, Sakai Tribes, Marginal People